2019
DOI: 10.3897/pharmacia.66.e35023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diosgenin and phenol compounds in Tribulus terrestris L.

Abstract: Caltrop (Tribulusterrestris L.) is a weed plant widely growing in warm climate. The crude caltrop has multidirectional pharmacological action favorable for the development of drug preparations. As in European countries caltrop is a non-officinal plant, it seems feasible to develop raw material standardization parameters for creation of novel drugs. In the course of thin layer chromatography research the following compounds were identified in caltrop herb purveyed during the fruiting season: rutin, chlorogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In the present study, the major active constituents from plants were found to be flavonoids, phenolics, terpenoids, and steroids, which is consistent with previous reports [12,59,60]. Furthermore, results from quantification studies showed there was a higher percentage of phenolic and flavonoid content in the methanolic extract compared with the aqueous extract.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the major active constituents from plants were found to be flavonoids, phenolics, terpenoids, and steroids, which is consistent with previous reports [12,59,60]. Furthermore, results from quantification studies showed there was a higher percentage of phenolic and flavonoid content in the methanolic extract compared with the aqueous extract.…”
Section: Discussionsupporting
confidence: 92%